2012
DOI: 10.1055/s-0032-1322595
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Bilateral Multiple Carotid-Cavernous Fistulas in a Patient with Ehlers-Danlos Syndrome

Abstract: In the management of multiple CCFs in EDS IV patients, we are able to occlude the fistulas and leave the ICA intact by using transarterial balloon-assisted embolization. Intensive follow-up of treated arteries is mandatory, because EDS IV is widespread and can occur on contralateral vessels as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Pepin et al reported an overall mean age of 30.9 years in 27 patients. Five (5.2%) patients [ 18 , 40 , 46 , 47 , 50 ] experienced a direct sCCF recurrence on the contralateral ICA 2.5 years, IQR [2.0–3.5] after the first fistula. Of 97 patients, 4 (4.1, 75.0% male) were diagnosed either with a direct CCF following minor trauma [ 7 , 11 , 14 ] or with an iatrogenic direct CCF after placement of a Fogarty balloon into the cavernous segment of the ICA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pepin et al reported an overall mean age of 30.9 years in 27 patients. Five (5.2%) patients [ 18 , 40 , 46 , 47 , 50 ] experienced a direct sCCF recurrence on the contralateral ICA 2.5 years, IQR [2.0–3.5] after the first fistula. Of 97 patients, 4 (4.1, 75.0% male) were diagnosed either with a direct CCF following minor trauma [ 7 , 11 , 14 ] or with an iatrogenic direct CCF after placement of a Fogarty balloon into the cavernous segment of the ICA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 Glycine missense variants [ 5 , 8 , 18 , 51 , 53 ] and 4 splice-site variants [ 8 , 29 , 45 , 51 ]. In the other patients, vEDS diagnosis was made either on relevant clinical examination, imaging and medical history [ 6 , 7 , 9 , 10 , 12 , 15 , 19 , 27 , 28 , 30 , 31 , 33 , 34 , 39 , 42 , 46 50 , 52 ], histological findings [ 6 , 9 , 24 , 27 , 32 , 43 , 44 , 47 ] or on fibroblast culture [ 8 , 15 , 36 , 38 , 40 , 43 , 44 ]. Imaging described marked tortuosity or dysplastic aspect or ectasia of the ICA segment in the neck [ 6 , 10 , 19 , 26 , 39 , 49 ], sometimes associated with an aneurysm rupture of the intracranial ICA segment into the CS [ 8 , 15 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Pepin et al., 44 out of the 419 patients with EDS IV had arterial complications of the central nervous system, with the most frequent being CCF. 40,130 There are several case studies that present CCF in EDS, 131138 with some discussing difficulties and death associated with the treatment of EDS IV patients with extreme vessel fragility. 130,139149 CCF have also been reported in the setting of Marfan syndrome.…”
Section: Other Neurovascular Manifestationsmentioning
confidence: 99%